Facial Skin Aging Stages in Chinese Females - Yang, Xiao-xiao; Zhao, Meng-meng; He, Yi-fan; Meng, Hong; Meng, Qing-yang; Shi, Qiao-yin; Yi, Fan (Frontiers in Medicine, 2022)
Background: Facial skin is exposed to the environment, which marks it with obvious signs of ageing. Based on multi-dimensional non-invasive evaluation data, female facial skin can be characterized in detail. However, there are few studies on the general ageing rules of facial skin. Most skin ageing studies divide the ages into 5-10-year intervals, so they have lacked dynamic matching with facial skin ageing. Aim: To explore facial skin ageing rules, discuss the main parameters of facial skin ageing, propose an unequal-distance ageing division method based on the main skin parameters, and study the skin characteristics of Chinese women of different ageing stages. Methods: We comprehensively described the skin status as 24 non-invasive skin parameters belonging to five dimensions: skin wrinkles, texture, stain, colour and barrier function. We performed polynomial fitting on the 21 skin parameters that were significantly correlated with age and derived the rules of ageing in the different dimensions. Based on the wrinkle dimension, the facial skin ageing process was divided into four stages, and the skin characteristics of the different stages were compared. Results: Skin wrinkles increased, texture deteriorated, acne decreased, pigment spots increased, skin tone darkened, and sebum secretion decreased with age, according to the polynomial fitting. The ageing stage was divided into an incubation period (18-30 years old), an ageing occurrence period (31-42 years old), a rapid ageing period (43-47 years old), and a stable ageing period (48-60 years old), according to the wrinkles. Different ageing stages had different skin characteristics. Conclusions: The incubation period is the critical period for the appearance of skin stains; the skin texture gradually deteriorates during the ageing occurrence period; the rapid ageing period is a critical period for the ageing of skin parameters; skin status during the stable ageing period is the worst.